Sistem Pendukung Keputusan Pemilihan Barista Coffee Terbaik Menerapkan Metode Multi Objective Optimization on The Basis of Ratio Analysis (MOORA) dan ROC - Rima Tamara Aldisa (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Coffee is a drink produced from seed plants which are roasted and then brewed into a drink that is enjoyed by all people in the world, including in Indonesia. Based on a survey that has been conducted, coffee is even a necessity for almost the entire community. The human habit of consuming coffee seems to be seen as an opportunity by some entrepreneurs. This is evident from the many coffee shops or hangouts that circulate in almost all corners of the city. The development of the coffee shop also gave rise to several terms such as cafe, place, or several other terms. Cafes usually have several employees including baristas, cashiers and others. However, what influences the development of the cafe the most is the quality of the baristas. If a barista at the cafe is a barista who is good at brewing coffee, people who like the brew will come back to enjoy the coffee again. But if not then the place will be empty of visitors. So that it greatly affects the development of the cafe that is being managed. The problem is choosing the best coffee barista will work if it's not computerized. There fore we need a system that can help those who are in need of assistance in making decisions. The solution is to use a decision support system (SPK). Decision support systems are computer-based systems and require methods. The method used is the MOORA method and the ROC method. by applying the ROC method and the MOORA method, it produces a value of 0.2608 on behalf of Diki Aji as an alternative to A1 which is the best choice with the highest score. So based on this research, it was decided that the best Barista Coffee was Diki Aji